Polymorphism of the TRAP gene of Plasmodium falciparum. - Robson, K; Hall, JR; Davies, L; Crisanti, A; Hill, A; Wellems, T (1990)
Natural sequence variation of the thrombospondin related anonymous protein (TRAP) gene of Plasmodium falciparum has been investigated by DNA analysis following the polymerase chain reaction amplification, and this shows the gene to be highly polymorphic. The region containing the sequence motif Trp-Ser-Pro-Cys-Ser-Val-Thr-Cys-Gly (WSPCSVTCG), common to TRAP, the circumsporozoite protein, properdin, and thrombospondin, was invariant. Elsewhere in the molecule, over 50 amino acid substitutions are described including the insertion of an in-frame, small-variable tandemly repeating motif between amino acid residues 352 and 353. Only one silent mutation was observed. Most nucleotide changes that occur in the first two codon positions result in conservative amino acid changes. Restriction fragment length polymorphism (RFLP) analysis was used to examine inheritance of TRAP in a cross between the HB3 and 3D7 clones of P. falciparum. Out of nine progeny examined, four possessed the HB3 gene and five the 3D7 gene. The TRAP gene hybridized to chromosome 13. Previous work has shown that a subtelomeric region of chromosome 13 from the 3D7 parent (marked by the HRP-III gene) was favoured strongly in this cross. The TRAP gene, however, is over 1 Mb away from this subtelomeric region and exhibits no such linkage because of chromosome crossovers. Five geographically separate isolates shared the same TRAP sequence as well as the same variant of the Th2R/Th3R region from the circumsporozoite protein. The correlation between independent markers in these isolates suggests that they have a common provenance.